2009
DOI: 10.1007/s00125-009-1347-2
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in human type 2 diabetes pancreatic beta cells

Abstract: Aims/hypothesis Beta cell loss contributes to type 2 diabetes, with increased apoptosis representing an underlying mechanism. Autophagy, i.e. the physiological degradation of damaged organelles and proteins, may, if altered, be associated with a distinct form of cell death. We studied several features of autophagy in beta cells from type 2 diabetic patients and assessed the role of metabolic perturbation and pharmacological intervention. Methods Pancreatic samples were obtained from organ donors and isolated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
256
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(288 citation statements)
references
References 15 publications
29
256
1
2
Order By: Relevance
“…hyperglycaemia, elevated NEFA and human islet amyloid polypeptide [hIAPP], and inflammation) affects autophagy and its impact on beta cell function also remains controversial. Several studies have shown that NEFA inhibit the expression of lysosome enzymes [78], lysosomal acidification and autophagic flux [81]. Similarly, the amyloidogenic peptide hIAPP has been found to inhibit autophagy [82].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…hyperglycaemia, elevated NEFA and human islet amyloid polypeptide [hIAPP], and inflammation) affects autophagy and its impact on beta cell function also remains controversial. Several studies have shown that NEFA inhibit the expression of lysosome enzymes [78], lysosomal acidification and autophagic flux [81]. Similarly, the amyloidogenic peptide hIAPP has been found to inhibit autophagy [82].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
“…As an example, Danon disease (OMIM: 300257) results from lysosome-associated membrane protein-2 (LAMP-2) deficiency, which disrupts the maturation of autophagosomes and their fusion with lysosomes, hence impairing autophagy [86]. This results in autophagic vacuole accumulation in various tissues, including liver, pancreas, muscle and heart [87], resembling the findings in human diabetic islets [78]. Without monitoring the autophagic flux, these findings could be erroneously interpreted as stimulation of autophagy.…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…20) The exact role and the regulation of autophagy in diabetes are still controversial. 21) While it is reported that autophagic cell death was enhanced in type-2 diabetes pancreatic beta cells, 22) most studies claimed that impaired autophagy was associated with the accumulation of dysfunctional or damaged cellular components, contributing to cellular dysfunction. 20) In our present study, we reported the increased autophagy in hyper-glycemic environment.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Cells were considered dead on the basis of the following criteria: loss of plasma membrane integrity, fragmentation into discrete bodies, engulfment of cell corpse, or its fragments by an adjacent cell. The presence of marked chromatin condensation or blebs was considered to be a sign of apoptosis.…”
Section: Cell Death Analysismentioning
confidence: 99%